Shifting into Higher Gear : Recommendations for Improved Grain Logistics in Ukraine - World Bank Group (World Bank, Washington, DC, 2015)
This study was conceived on the basis of a request by Ukraine’s Ministry of Agricultural Policies and Food (MoAPF). In 2013, the MoAPF explored the World Bank’s interest for investing in grain hoppers, following a deficit of hoppers and concerns about related difficulties for grain transport. In response, the World Bank secured resources from the Multi Donor Trust Fund for Trade and Development (TF016693) to carry out a review of grain logistics in Ukraine in order to better understand the challenges facing the sector. The objectives of this report are to assess the functioning of the grain logistics system, identify bottlenecks and put forward practical recommendations for investments and reform. Research points to five key drivers of current high logistics costs: (i) lack of regulatory clarity and sub-optimal management of public assets that create barriers to private investments; (ii) underutilization of river transport, (iii) underinvestment in rail transport; (iv) inefficiencies in storage management, and (v) excessive use of road transport. However, there are two important limitations of the report that should be taken into account. First, the ongoing crisis remains a source of uncertainty. It has so far had limited impact on grain production and logistics, yet access to finance has become more difficult and other impacts might arise in the future. Second, there are two areas that the report does not address: customs and ports. Both are important elements of logistics costs and deserve a comprehensive analysis in the future.